Divergence in aerobic scope and thermal tolerance is related to local thermal regime in two populations of introduced Nile perch (Lates niloticus). Issue 1 (12th May 2020) - Nyboer, Elizabeth A.; Chrétien, Emmanuelle; Chapman, Lauren J.
Abstract: We tested whether thermal tolerance and aerobic performance differed between two populations of Nile perch ( Lates niloticus ) originating from the same source population six decades after their introduction into two lakes in the Lake Victoria basin in East Africa. We used short‐term acclimation of juvenile fish to a range of temperatures from ambient to +6°C, and performed critical thermal maximum (CTmax ) and respirometry tests to measure upper thermal tolerance, resting and maximum metabolic rates, and aerobic scope (AS). Across acclimation temperatures, Nile perch from the cooler lake (Lake Nabugabo, Uganda) tended to have lower thermal tolerance ( i.e., CTmax ) and lower aerobic performance ( i.e., AS) than Nile perch from the warmer waters of Lake Victoria (Bugonga region, Uganda). Effects of temperature acclimation were more pronounced in the Lake Victoria population, with the Lake Nabugabo fish showing less thermal plasticity in most metabolic traits. Our results suggest phenotypic divergence in thermal tolerance between these two introduced populations in a direction consistent with an adaptive response to local thermal regimes.